2022
DOI: 10.1038/s41420-022-01281-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-5 Eg5 is essential for spindle assembly, chromosome stability and organogenesis in development

Abstract: Chromosome stability relies on bipolar spindle assembly and faithful chromosome segregation during cell division. Kinesin-5 Eg5 is a plus-end-directed kinesin motor protein, which is essential for spindle pole separation and chromosome alignment in mitosis. Heterozygous Eg5 mutations cause autosomal-dominant microcephaly, primary lymphedema, and chorioretinal dysplasia syndrome in humans. However, the developmental roles and cellular mechanisms of Eg5 in organogenesis remain largely unknown. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…KSP is a plus-end directed kinesin essential for bipolar spindle formation, and it was suggested that its overexpression in mice can lead to genomic instability and tumor development [ 12 , 14 ]. Its inhibition leads to the formation of monopolar spindles, activation of SAC, and consequently, mitotic arrest typically followed by cell death [ 11 , 14 ]. While Aurora B is a serine-threonine protein kinase member of the Aurora kinases family involved in correct chromosomal segregation and was shown to be overexpressed in poorly differentiated and metastasized OSCC [ 16 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KSP is a plus-end directed kinesin essential for bipolar spindle formation, and it was suggested that its overexpression in mice can lead to genomic instability and tumor development [ 12 , 14 ]. Its inhibition leads to the formation of monopolar spindles, activation of SAC, and consequently, mitotic arrest typically followed by cell death [ 11 , 14 ]. While Aurora B is a serine-threonine protein kinase member of the Aurora kinases family involved in correct chromosomal segregation and was shown to be overexpressed in poorly differentiated and metastasized OSCC [ 16 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…KSP, also known as Eg5 and Kif11, is a kinesin-5 family member essential for bipolar mitotic spindle formation, microtubule cross-linking, and chromosome alignment [ 11 , 12 , 13 ]. The overexpression of KSP is associated with poor outcomes in breast and laryngeal cancers and its inhibition leads to the formation of monopolar spindles, activation of the spindle assembly checkpoint (SAC), and consequently, mitotic arrest followed by cell death [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The function of generated Eg5 protein in genetic MCLID KIF dependent gene is, of course, compromised: the microcephaly symptom could be due to the reduced activity of Eg5 in spindle formation, being this protein essential for organogenesis in general [ 3 ] and for neural development in particular [ 109 ]. However, the importance of KIF11 activity in the development and maintenance of retinal and lymphatic structures was highlighted by the fact that mutations in this gene were also detected in patients with chorioretinopathy and/or lymphedema, in addition to the microcephaly condition, supported by the finding that KIF11 is also localized in the inner segment and ciliary compartments of murine retina photoreceptor cells [ 110 ].…”
Section: Eg5 In Noncancerous Diseasesmentioning
confidence: 99%
“…Between the prophase and prometaphase, the mitotic spindle MTs, starting from the two centrosomes, extend across the cell cytoplasm. Eg5 reaches maximum concentration during these steps; thanks to its homotetrameric structure, anchors itself to the plus end extremity of interpolar MTs, allowing its overlapping at the equator of the cell and, at the same time, the separation of the two centrosomes at the opposite poles of the cell [ 2 , 3 ]. To allow bipolar spindle formation, different mechanisms of action coexist, such as phosphorylation or deacetylation of different Eg5 sites [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation